The impact of natural disasters on the work of international organizations - the 2014 tsunami disaster as a case study - امين, جمال محمد; سمين, نيان والي (Sulaimani Journal for Humanities, 2019)
Natural disasters are the disasters resulting from a sharp change in the nature of the surrounding environment beyond human capacity. The tsunami is one of the biggest natural disasters in the world that can not be accurately predicted, as noted by geologists and oceanographers, and seismologists. Despite the tremendous scientific progress that humans have reached, they are still powerless and unable to resist the fury of destructive natural disasters that have varied and multiplied, such as volcanoes, earthquakes, avalanches, water disasters, hurricanes and tsunami. Tsunami is a great threat to human life, especially in the seaside countries, causing great loss of life and property from ancient times until now. This natural disaster can exterminate an entire nation, which had already happened in many East Asian countries. Especially the tsunami that hit a number of Asian countries in 2004, leaving a huge number of dead, wounded and displaced people.
Keywords: Tsunami disaster; international relations; international organizations; United Nations